Histochemical Comparison of the Hypopharyngeal Gland in Apis cerana Fabricius, 1793 Workers and Apis mellifera Linnaeus, 1758 Workers - Guntima Suwannapong; Saichon Chaiwongwattanakul; Mark Eric Benbow (Psyche: A Journal of Entomology)
Hypopharyngeal glands of honeybee are age-dependent structures that change with the size of acini and are correlated with various social behaviors. The histochemical structure of Apis cerana and A. mellifera worker hypopharyngeal glands in four different developmental stages wes stained with ninhydrin Schiff's and periodic acid Schiff's reagents (PAS) for localization of proteins and carbohydrates, respectively, and examined with light microscopy. Nurse bees of both honeybee species had significantly larger glands as compared to guards and forgers, but there were no statistically significant differences between these two species after accounting for caste. Gland protein concentration increased progressively in nurse bees, and this was correlated with the appearance of enriched protein granules in the cytoplasm. In addition, the hypopharyngeal gland protein concentration of A. mellifera was higher than that of A. cerana even though gland size was not significantly different between species. However, gland size was shown to have decreased progressively in foragers and guards.